When will it end? Long-lived intracontinental reactivation in central Australia - Quentin de Gromard, R.; Kirkland, Chris; Howard, H.; Wingate, M.; Jourdan, Fred; McInnes, Brent; Danišík, Martin; Evans, Noreen; McDonald, B.; Smithies, R. (Elsevier, 2018)
The post-Mesoproterozoic tectonometamorphic history of the Musgrave Province, central Australia, has previously been solely attributed to intracontinental compressional deformation during the 580–520 Ma Petermann Orogeny. However, our new structurally controlled multi-mineral geochronology results, from two north-trending transects, indicate protracted reactivation of the Australian continental interior over ca. 715 million years. The earliest events are identified in the hinterland of the orogen along the western transect. The first tectonothermal event, at ca. 715 Ma, is indicated by 40Ar/39Ar muscovite and U–Pb titanite ages. Another previously unrecognised tectonometamorphic event is dated at ca. 630 Ma by U–Pb analyses of metamorphic zircon rims. This event was followed by continuous cooling and exhumation of the hinterland and core of the orogen along numerous faults, including the Woodroffe Thrust, from ca. 625 Ma to 565 Ma as indicated by muscovite, biotite, and hornblende 40Ar/39Ar cooling ages. We therefore propose that the Petermann Orogeny commenced as early as ca. 630 Ma. Along the eastern transect, 40Ar/39Ar muscovite and zircon (U–Th)/He data indicate exhumation of the foreland fold and thrust system to shallow crustal levels between ca. 550 Ma and 520 Ma, while the core of the orogen was undergoing exhumation to mid-crustal levels and cooling below 600–660 °C. Subsequent cooling to 150–220 °C of the core of the orogen occurred between ca. 480 Ma and 400 Ma (zircon [U–Th]/He data) during reactivation of the Woodroffe Thrust, coincident with the 450–300 Ma Alice Springs Orogeny. Exhumation of the footwall of the Woodroffe Thrust to shallow depths occurred at ca. 200 Ma. More recent tectonic activity is also evident as on the 21 May, 2016 (Sydney date), a magnitude 6.1 earthquake occurred, and the resolved focal mechanism indicates that compressive stress and exhumation along the Woodroffe Thrust is continuing to the present day. Overall, these results demonstrate repeated amagmatic reactivation of the continental interior of Australia for ca. 715 million years, including at least 600 million years of reactivation along the Woodroffe Thrust alone. Estimated cooling rates agree with previously reported rates and suggest slow cooling of 0.9–7.0 °C/Ma in the core of the Petermann Orogen between ca. 570 Ma and 400 Ma. The long-lived, amagmatic, intracontinental reactivation of central Australia is a remarkable example of stress transmission, strain localization and cratonization-hindering processes that highlights the complexity of Continental Tectonics with regards to the rigid-plate paradigm of Plate Tectonics.